Analisis Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Properti dan Real Estate yang Go Public di BEI Tahun 2006 – 2011) - Yuni Sartika Sitorus; Irsutami Irsutami (JURNAL INTEGRASI, 2013)
The aim of this study was to analyze whether working capital management which consist of average collection period, inventory turnover in days, and average payment period has an influence on the company’s profitability as measured using ROI. Samples were taken using a purposive samppling method, in order to get 12 companies as a sample which consist of 72 observation. Influencee of independent variable such as average collection period, inventory turnover in days, and average payment period to ROI investigated using regression analysis method. The result showed that there are three variable that average collection period, inventory turnover in days, and average payment period has a significant negative effect on ROI.